A systematic review of the use of Acceptance and Commitment Therapy (ACT) in chronic disease and long-term conditions. (June 2016) - Graham, Christopher D.; Gouick, Joanna; Krahé, Charlotte; Gillanders, David
Abstract: Many have proposed that Acceptance and Commitment Therapy (ACT) may be particularly effective for improving outcomes in chronic disease/long-term conditions, and ACT techniques are now being used clinically. However, reviews of ACT in this context are lacking, and the state of evidence is unclear. This systematic review aimed to: collate all ACT interventions with chronic disease/long-term conditions, evaluate their quality, and comment on efficacy. Ovid MEDLINE, EMBASE and Psych Info were searched. Studies with solely mental health or chronic pain populations were excluded. Study quality was then rated, with a proportion re-rated by a second researcher. Eighteen studies were included: eight were randomised controlled trials (RCTs), four used pre–post designs, and six were case studies. A broad range of applications was observed (e.g. improving quality of life and symptom control, reducing distress) across many diseases/conditions (e.g. HIV, cancer, epilepsy). However, study quality was generally low, and many interventions were of low intensity. The small number of RCTs per application and lower study quality emphasise that ACT is not yet a well-established intervention for chronic disease/long-term conditions. However, there was some promising data supporting certain applications: parenting of children with long-term conditions, seizure-control in epilepsy, psychological flexibility, and possibly disease self-management. Highlights: A growing body of work (18 studies) has evaluated ACT in long-term conditions. Study quality is mostly low. As ACT is used clinically, high-quality RCTs are needed. Some promising evidence for parenting of children with LTCs, seizure control, psychological flexibility, self-management.